2008
DOI: 10.1029/2007jb005002
|View full text |Cite
|
Sign up to set email alerts
|

Effective stress and pore pressure in the Nankai accretionary prism off the Muroto Peninsula, southwestern Japan

Abstract: [1] We developed a theoretical method for predicting effective stress and pore pressure based on rock physics model. We applied the method to reveal the pore pressure distribution within the Nankai accretionary prism off southwestern Japan and to investigate variations in pore pressure associated with evolution of the plate boundary décollement. From the crack aspect ratio spectrum estimated from laboratory and well-log data, we calculated a theoretical relationship between acoustic velocity and mean effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 92 publications
5
78
1
Order By: Relevance
“…These values of ψ result in excess pore pressures at 75 m below the décollement increasing from ∼2.1 to 37.0 MPa, from the trench to 40 km landward (Figure 8c). For comparison, a study by Tsuji et al [2008], using a method similar to that of Tobin and Saffer [2009] reported excess pore pressure beneath the décollement increasing from ∼5–20 MPa from the trench to ∼20 km landward.…”
Section: Resultsmentioning
confidence: 99%
“…These values of ψ result in excess pore pressures at 75 m below the décollement increasing from ∼2.1 to 37.0 MPa, from the trench to 40 km landward (Figure 8c). For comparison, a study by Tsuji et al [2008], using a method similar to that of Tobin and Saffer [2009] reported excess pore pressure beneath the décollement increasing from ∼5–20 MPa from the trench to ∼20 km landward.…”
Section: Resultsmentioning
confidence: 99%
“…Although these Paleozoic rocks dominate the surface geology, outcrops of Triassic plutons lie along the coastline. Some of these intrusions contain fayalite, indicating a mantle-derived magmatic source (Vásquez and Franz, 2008). The intrusions were emplaced when the margin was undergoing post-orogenic collapse and rifting, marking the transitional period between Gondwanan amalgamation and contemporary Andean-style subduction (Vásquez et al, 2011).…”
Section: Characteristics Of the Central Chile Subduction Zonementioning
confidence: 99%
“…Research has long shown that velocity shows dependency on static stress conditions [e.g., Toksöz et al, 1976;Christensen and Wang, 1985;Tsuji et al, 2008]. Several studies have observed the velocity change associated with stress change due to earthquakes by using multiplet earthquake analysis [e.g., Poupinet et al, 1984] or controlled source experiments [e.g., Nishimura et al, 2000;Niu et al, 2008].…”
Section: Introductionmentioning
confidence: 99%